Effects of Different Cultural Backgrounds and Co-ethnicity on Interpersonal Interactions among Students from Different Cultures and Nationalities at a Malaysian Public University - Sarwari, Abdul Qahar; Ainol Haryati, Ibrahim; Nor Ashikin, Abdul Aziz (Iosrjournals.org, 2014)
TThis study was conducted to evaluate the effects of different cultural backgrounds and co-ethnicity on the process of interpersonal communication (IPC) among local and international students of University Malaysia Pahang (UMP). An embedded design of mixed methods was applied to conduct this study. The quantitative survey was conducted as the main method of this study and the qualitative interviews were done to enrich the data. The quantitative survey had 220 participants from both Malaysian and international students of UMP, and 12 of them were interviewed for the qualitative data as well. According to the results, the vast majority of participants reported that their different cultural backgrounds had positive effects on their interactions with students from different nationalities and their interactions with different people enabled them to gain some new cultural information. Findings of this study also confirmed the helpful influence of coethnicity on interactions among students who had students from their own ethnicities and tribes among local or foreign students of UMP. The results are supportive of the positive effects of cultural and tribal diversities of both local and international students of UMP on their daily interactions. Findings of this study may encourage university students to be involved in interactions with students from different cultures and ethnicities to experience the new multicultural environments and improve their social skills through their interactions with people from different societies.